The Role of Female Farm Workers in Improving Family Welfare In Barugae Village, Mallawa District, Maros Regency - Hariashari Rahim; Sakaria Anwar; Muh Sabiq; Aisyah Yulindasari (Department of Sociology Faculty of Social and Political Sciences, 2022)
This study aims to analyze the extent of the economic contribution of female farmworkers in families in Barugae Village, Mallawa District, Maros Regency in improving family welfare. The problem of living needs in the family is increasing, the prices of basic necessities are getting higher, plus the needs of children when entering the school period requires the head of the family to increase his income so that it can meet the needs of the family, especially the fulfillment of primary needs. This study involved female farmworkers who had families and contributed to the welfare of the family. The results showed that the improvement in the welfare of women farmworkers' families in Barugae Village, Mallawa District, Maros Regency, was influenced by several things, namely the level of income received by female farm workers, improved welfare in the families of female farmworkers, the gender roles of female farmworkers who not only perform domestic roles but also public and community roles and the contribution of female farmworkers in the family both household and economic contributions.